Micron-flower-like NiCo-MOF electrode material, and preparation method and application thereof

CN122930741APending Publication Date: 2026-10-16QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611033435.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]针对现有NiCo-MOF电极材料的面积比电容和倍率较低,以及与其他材料复合制备工艺复杂、不易大规模生产等问题

Benefits of technology

(1) 本发明所制备泡沫镍负载微米花状NiCo-MOF电极材料的制备方法是,首先将泡沫镍在较低温度10~60°C下浸泡反应较短时间,在导电基片上生长初生的均匀蜂窝状NiCo-MOF纳米片阵列,这为后续溶剂热法生长微米花状NiCo-MOF材料提供很好的形核和生长条件;然后进行溶剂热反应,这两步反应之间不需要进行清洗和干燥,大大节约材料的制备时间和清洗成本。制备工艺简单、能耗低,便于大规模工业生产。泡沫镍作为导电基片原位生长活性材料,避免使用粘结剂和复杂的涂覆工艺。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930741A_ABST
    Figure CN122930741A_ABST
Patent Text Reader

Abstract

The application relates to a micrometer flower-like NiCo-MOF electrode material and a preparation method and application thereof, wherein foam nickel is used as a matrix, Ni(NO3)2.6H2O, Co(NO3)2.6H2O and p-phenylenediamine are sequentially dissolved in dimethylformamide and deionized water to obtain a mixed solution, a primary honeycomb-like NiCo-MOF is obtained by first soaking and reacting at a lower temperature, and then a solvent thermal reaction is carried out to synthesize the micrometer flower-like NiCo-MOF electrode material loaded on the foam nickel, which has a unique three-dimensional layered structure. The structure has a large specific surface area and can provide rich electroactive sites; the holes between the micrometer flowers and the large open spaces between the nanosheets are beneficial to the rapid penetration and diffusion of ions of an electrolyte in an electrochemical reaction process, more active materials can fully participate in pseudo-capacitance reactions, excellent area specific capacitance and high rate performance can be provided, and the micrometer flower-like NiCo-MOF electrode material can be applied to a next-generation high-performance supercapacitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of novel energy storage materials and nanomaterial synthesis technology, specifically relating to a micron-sized flower-shaped NiCo-MOF electrode material, its preparation method, and its application in supercapacitors. Background Technology

[0002] The excessive consumption of fossil fuels globally has led to energy shortages and exacerbated the greenhouse effect, making the development and utilization of clean, environmentally friendly, and renewable energy a global consensus. my country's "dual carbon" goals provide significant development opportunities for the large-scale development and efficient utilization of renewable energy. While solar and wind power are clean and environmentally friendly renewable energy sources, their intermittent and fluctuating nature affects the stability of the grid, making high-performance energy storage technology a crucial solution. Simultaneously, the rapid development of new energy electric vehicles, smart grid energy storage, and portable electronic devices places higher demands on the energy density, power density, cycle stability, and environmental friendliness of energy storage devices. Therefore, developing efficient and low-cost new energy storage and conversion devices has become an urgent need and a research hotspot in the energy storage field.

[0003] Supercapacitors, as a novel energy storage device between traditional capacitors and batteries, possess advantages such as high power density, rapid charge and discharge, long cycle life, wide operating temperature range, and safety and environmental friendliness. They have broad application prospects in fields such as regenerative braking, emergency power supplies, and auxiliary power for new energy vehicles. Supercapacitors are divided into electric double-layer capacitors and pseudocapacitors. The former uses activated carbon as the electrode material and exhibits excellent cycle stability but has a very low specific capacitance, with an energy density of only 5-10 Wh / kg. -1 It is far lower than the 150~300Wh / kg of lithium batteries. -1 In contrast, the current method cannot meet the requirements for high energy density energy storage; while pseudocapacitors store charge through Faraday redox reactions, and have higher specific capacitance and energy density. Therefore, pseudocapacitors are an important research direction for improving the performance of supercapacitors.

[0004] Electrode material performance is crucial for determining the energy storage capacity of pseudocapacitors. While extensive research has been conducted on cathode materials, their capacity remains relatively low, directly and significantly impacting the energy density of assembled asymmetric supercapacitor devices. Common cathode materials include transition metal oxides / hydroxides / sulfides, conductive polymers, and metal-organic frameworks (MOFs). Among these, MOFs, composed of metal ions / clusters coordinated with organic ligands, possess high specific surface area and abundant active sites. Ni and Co are preferred due to their high electroactivity and good conductivity. NiCo-MOFs exhibit superior capacity, conductivity, and energy storage capacity compared to single-metal MOFs due to their bimetallic synergistic effect, and their morphology and porosity are tunable. Currently, researchers have conducted some studies on metal-organic framework electrode materials. Yang et al. synthesized NiCo-MOF nanosphere electrode materials using a microwave-assisted method at a current density of 1 A g / L. -1 The specific capacitance at that time was 1128 F g. -1 (Xing Yang, Xin Zhang, Ning Yang, et al. NiCo-MOF Nanospheres Created by the Ultra-Fast Microwave Method for Use in High-Performance Supercapacitors. Molecules, 2023, 28: 5613). Zhang et al. prepared NiCo-MOF@Ni-LDH composite electrode materials using a hydrothermal method at a current density of 1 A g. -1 The specific capacitance at that time was 1880 F g. -1 20A g -1 The capacitance retention was 67.0% at a current density of 5 mA cm⁻¹ (Jiawei Zhang, Yuxin Li, Haobo Li, et al. Three-Dimensional Porous Flower-like NiCo-MOF@Ni-LDH Composite Electrode for High-Performance Supercapacitors. ACS Applied Energy Materials, 2024, 7: 14374-14382). Jiang Zichao et al. prepared NiCo-MOF / MXene composite materials on nickel foam using an in-situ synthesis method, achieving a capacitance retention of 67.0% at a current density of 5 mA cm⁻¹. -2 The areal capacitance at that time was 4.96 F cm⁻¹. -2(Jiang Zichao, Peng Haining, Chen Qizhi, et al. Study on capacitive properties of in-situ synthesized NiCo-MOF / MXene materials. Journal of Nanhua University (Natural Science Edition), 2024, 38(1): 72-79). Huang et al. first prepared Co(OH)2 by electrodeposition, and then used Co(OH)2 as a template to grow nano-NiCo-MOF on nickel foam by solvothermal method. The results were obtained at a current density of 1 mA cm⁻¹. -2 The areal capacitance at that time was 5.84 F cm⁻¹. -2 (Simin Huang, Xue-Rong Shi, Chunyan Sun, et al. Template-controlled in-situ growing of NiCo-MOF nanosheets on Ni foam with mixed linkers for high performance asymmetric supercapacitors. Applied Surface Science, 2022, 572: 151344). Xiang et al. prepared NiCo-MOF / NiO heterojunction nanosheets using a hydrothermal method combined with atomic layer deposition, achieving high performance at a current density of 5 mAcm⁻¹. -2 The areal capacitance at that time was 3.01 F cm⁻¹. -2 (Jiayuan Xiang, et al. Nano-thin heterogeneousNiCo MOF / NiO nanosheets for high-rate energy storage. Surface and CoatingsTechnology, 2025, 496: 131781).

[0005] Although some progress has been made in the research of NiCo-MOF electrode materials, certain limitations still exist: ① The specific capacitance of nano-NiCo-MOF materials has been improved to some extent, but it is still relatively low, especially the areal specific capacitance, which is below 5 F cm⁻¹. -2 ② Existing electrode materials exhibit relatively high capacity at low current densities but low capacity at high current densities, meaning they have low rate performance, which severely restricts their widespread application at high currents. ③ Some high-capacity composite electrode materials are combined with metal hydroxides, MXenes, and metal oxides, resulting in complex preparation processes that are not conducive to large-scale production. Therefore, developing a simple, energy-efficient, and environmentally friendly preparation process for metal-organic framework (MOF) cathode materials, which simultaneously possess excellent areal specific capacitance and high rate performance, is crucial for significantly improving the capacity and energy density of supercapacitors. Summary of the Invention

[0006] To address the issues of low areal capacitance and rate capability of existing NiCo-MOF electrode materials, as well as the complexity of their composite fabrication processes and the difficulty in large-scale production, this invention aims to provide a high-performance micron-shaped NiCo-MOF electrode material, its preparation method, and its applications. The prepared electrode material possesses a large specific surface area and a three-dimensional hierarchical structure with multi-level pores, providing outstanding areal capacitance and high rate capability. It can be directly used as a binder-free, next-generation high-performance supercapacitor electrode material.

[0007] To achieve the objective of this invention, the technical solution of this invention is a micron-sized flower-like NiCo-MOF electrode material and its preparation method, comprising the following preparation steps: (1) A certain size of nickel foam is placed in 3 mol L -1 The surface oxides and impurities were removed by ultrasonic cleaning in HCl solution for 12 minutes. Then, the surface was ultrasonically cleaned and immersed in deionized water and anhydrous ethanol, respectively. Finally, it was dried in a forced-air drying oven to obtain pretreated nickel foam. (2) Add a certain volume of N,N-dimethylformamide solution to Ni(NO3)2·6H2O, Co(NO3)2·6H2O and terephthalic acid powder reagents, stir magnetically for 20 min until completely dissolved, then add a certain volume of deionized water, stir with a glass rod for 2 min to obtain a uniform mixed solution. (3) The above mixed solution was transferred into the polytetrafluoroethylene liner of the reactor and pretreated nickel foam was added. After the reactor was sealed, it was placed in a drying oven and soaked at a low temperature to obtain nascent nano-NiCo-MOF grown on the surface of nickel foam. (4) The reaction vessel was heated to a high temperature in a forced-air drying oven to carry out a solvothermal reaction. After cooling to room temperature, the nickel foam with active material was taken out and washed several times with deionized water and anhydrous ethanol respectively. Finally, it was dried in a drying oven at 60°C for 10 hours to obtain nickel foam-supported nano-NiCo-MOF electrode material. In step (2), the concentration of Ni(NO3)2·6H2O in the mixed solution is 0.05 mol / L. -1 The concentration of Co(NO3)2·6H2O is 0.025 mol / L. -1 The terephthalic acid content is 0.05 mol / L. -1 ; In step (2), the volume ratio of N,N-dimethylformamide to deionized water in the mixed solution is 9:1; In step (3), the soaking reaction temperature is 10~60°C and the reaction time is 0.5~4h; In step (4), the solvothermal reaction temperature is 150°C and the reaction time is 14h.

[0008] The beneficial effects of this invention are: (1) The preparation method of the nickel foam-supported micron-shaped NiCo-MOF electrode material prepared in this invention involves first immersing nickel foam in a relatively low temperature (10-60°C) for a short time to grow a nascent, uniform honeycomb-shaped NiCo-MOF nanosheet array on a conductive substrate. This provides excellent nucleation and growth conditions for the subsequent solvothermal growth of the micron-shaped NiCo-MOF material. Then, a solvothermal reaction is carried out. No cleaning or drying is required between these two steps, significantly saving preparation time and cleaning costs. The preparation process is simple, energy-efficient, and suitable for large-scale industrial production. Nickel foam, as an in-situ active material grown on a conductive substrate, avoids the use of binders and complex coating processes.

[0009] (2) The foamed nickel-supported micron flower-shaped NiCo-MOF electrode material prepared by the present invention has a unique three-dimensional layered structure, which includes a uniform honeycomb nanosheet array at the bottom layer and a micron flower array composed of a large number of nanosheets with rough surfaces stacked on the outside layer. They are grown in situ on a porous foamed nickel conductive substrate, have a large specific surface area, and can provide abundant electroactive sites. The pores between the micron flowers and the large number of open spaces between the nanosheets are conducive to the rapid penetration and efficient diffusion of ions in the electrolyte during the electrochemical reaction.

[0010] (3) The nickel foam-supported micron-shaped NiCo-MOF electrode material prepared in this invention has excellent areal capacitance and high rate performance, at a current density of 5 mA cm⁻¹. -2 The area capacitance is as high as 57.85 F / cm². -2 At a high current density of 50 mA cm -2 The capacitance retention rate was 75.13%, even at very high current densities of 150 mA / cm². -2 The areal capacitance is also as high as 27.07 F cm⁻¹. -2 This electrode material can be directly applied to next-generation high-performance supercapacitors, and also has certain application potential in lithium-ion batteries and electrocatalysis. Attached Figure Description

[0011] Figure 1 SEM images of nascent nano-NiCo-MOF grown on the surface of the nickel foam prepared in Example 1 at different magnifications.

[0012] Figure 2 SEM images of the nickel foam-supported nano-NiCo-MOF electrode material prepared in Example 1 at different magnifications.

[0013] Figure 3 Electrochemical performance of the nickel foam-supported nano-NiCo-MOF electrode material prepared in Example 1: (a) Cyclic voltammetry curves at different scan rates, (b) Constant current charge-discharge curves at different current densities, and (c) Area capacitance at different current densities.

[0014] Figure 4 The nickel-supported nano-NiCo-MOF electrode materials prepared in Examples 1-7 and Comparative Example 1 were tested at a current density of 5 mA cm⁻¹. -2 The constant current charge-discharge curve at that time. Detailed Implementation

[0015] To make the technical problem to be solved, the technical solution, and the beneficial effects of the present invention clearer, the present invention will be further described in detail below with reference to embodiments, comparative examples, and accompanying drawings. It should be understood that the embodiments described are only for explaining the present invention and are not intended to limit the scope of the present invention.

[0016] Example 1 (1) Place 2.2cm×6cm nickel foam in 3 mol L -1 The surface oxides and impurities were removed by ultrasonic cleaning in HCl solution for 12 min. Then, the surface was ultrasonically cleaned 3-5 times in deionized water until the solution was neutral. Finally, the surface was soaked and cleaned in anhydrous ethanol and then dried in a forced-air drying oven at 60°C for 50 min to obtain pretreated nickel foam. (2) Pour 2 mmol of Ni(NO3)2·6H2O, 1 mmol of Co(NO3)2·6H2O and 2 mmol of terephthalic acid into a beaker, add 36 mL of N,N-dimethylformamide solution, stir magnetically for 20 min until completely dissolved, then add 4 mL of deionized water, stir with a glass rod for 2 min to obtain a homogeneous mixed solution; (3) The mixed solution was transferred into the polytetrafluoroethylene liner of the reactor and pretreated nickel foam was added. After the reactor was sealed, it was placed in a drying oven and soaked at room temperature for 2 hours to obtain nascent nano-NiCo-MOF grown on the surface of nickel foam. (4) The reaction vessel was heated to 150°C in a forced-air drying oven and reacted for 14 hours. After cooling to room temperature, the nickel foam with active material was taken out and washed several times with deionized water and anhydrous ethanol. Finally, it was dried in a drying oven at 60°C for 10 hours to obtain nickel foam-supported nano-NiCo-MOF electrode material.

[0017] Figure 1 These are SEM images of the surface-grown nascent NiCo-MOF nanoparticles at different magnifications. Figure 1As can be seen in the lower magnification images (a) and (b), a large amount of nascent nano-NiCo-MOF material is uniformly grown on the surface of the nickel foam. Further analysis reveals... Figure 1 The magnified images in (c) and (d) clearly show that these nanomaterials are composed of a large number of interconnected nanosheets forming a porous, honeycomb-like nanosheet array. Notably, the surfaces of these nascent nanosheets are very rough, with a large surface area, which provides excellent nucleation and growth conditions for the subsequent solvothermal growth of micron-shaped NiCo-MOF materials.

[0018] Figure 2 Microscopic morphology images of nano-NiCo-MOF electrode materials grown using the solvothermal method. From Figure 2 As seen in the lower magnification images (a) and (b), the NiCo-MOF grown on the nickel foam surface exhibits a micron-flower-like morphology, with pores between the micron-flowers facilitating rapid electrolyte penetration and efflux. The magnified image (c) reveals that these micron-flowers are composed of a large number of interlaced nanosheets with open spaces between them. The high magnification image (d) clearly shows a large number of nanoparticles growing on the nanosheet surface, resulting in a very rough surface and a large specific surface area. Therefore, the prepared nano-NiCo-MOF electrode material comprises a uniform honeycomb nanosheet array at the bottom layer and an outer layer of micron-flower arrays composed of a large number of stacked, rough-surfaced nanosheets. These layers are grown in situ on a porous nickel foam conductive substrate, forming a unique three-dimensional layered composite structure of micron-flower-like NiCo-MOF electrode material. This composite structure provides a large specific surface area and abundant active sites for electrochemical reactions. The pores between the micron-flowers and the open spaces between the nanosheets not only serve as "reservoirs" for the electrolyte but also facilitate rapid infiltration and efflux during the electrochemical reaction, allowing more active materials to fully participate in the pseudocapacitive reaction. Simultaneously, it effectively mitigates the volume expansion of the material during charge and discharge, contributing to the structural stability of the electrode during long-term cycling. The prepared electrode material uses a Ni to Co molar ratio of 2:1. Ni provides abundant electroactive sites, while Co regulates the electronic structure and offers synergistic advantages of multiple components. Combined with the excellent electronic conductivity of the micron-flower MOF framework, this reduces the material's impedance and promotes rapid electron transport and transfer. Therefore, these advantages of the prepared nickel-foamed micron-flower MOF electrode material provide crucial structural and compositional guarantees for its outstanding capacity and high rate performance.

[0019] The electrochemical performance of the prepared nickel foam-supported micron-shaped NiCo-MOF electrode material was tested in a three-electrode system. The prepared NiCo-MOF electrode was used as the working electrode, platinum wire as the counter electrode, and Ag / AgCl electrode as the reference electrode. A 2 mol / L... -1The KOH aqueous solution is used as the electrolyte, and the main electrochemical performance tests include cyclic voltammetry curves and constant current charge-discharge curves.

[0020] The electrochemical performance of the prepared nickel foam-supported micron-shaped NiCo-MOF electrode material is shown in the figure. Figure 3 . Figure 3 (a) shows the cyclic voltammetry curves of the electrode material at different scan rates. Each curve has a distinct redox peak, indicating that a Faraday pseudocapacitive reaction occurs. Figure 3 (b) shows the constant current charge-discharge curves at different current densities. All curves have obvious potential plateaus, further proving that the electrode material undergoes redox reactions. Figure 2 (c) shows the areal capacitance curves at different current densities of 5, 10, 20, 30, 50, 70, 100, and 150 mA cm⁻¹. -2 The areal capacitances at the following times were 57.85, 55.2, 55.15, 48.11, 43.46, 39.87, 34.98, and 27.07 F / cm, respectively. -2 At a high current density of 50 mA cm⁻¹ -2 The capacitance retention rate was 75.13% at a very high current density of 150 mA cm⁻¹. -2 The area capacitance was also as high as 27.07 Fcm. -2 Therefore, the prepared nickel foam-supported micron-shaped NiCo-MOF electrode material exhibits outstanding areal capacitance and excellent rate performance, and avoids the use of binders and complex coating processes, showing great potential as a next-generation high-performance supercapacitor electrode material.

[0021] Example 2 Example 2 differs from Example 1 in that, in step (3), the reaction is carried out at room temperature for 1 hour, while other preparation conditions and processes are the same as in Example 1, resulting in a nickel foam-supported NiCo-MOF electrode material. Figure 4 The curve shows that the electrode operates at 5 mA cm⁻¹ -2 The areal capacitance at that time was 30.70 F / cm². -2 .

[0022] Example 3 Example 3 differs from Example 1 in that, in step (3), the reaction is carried out at room temperature for 3 hours, while other preparation conditions and processes are the same as in Example 1, resulting in a nickel foam-supported NiCo-MOF electrode material. Figure 4 The curve shows that the electrode operates at 5 mA cm⁻¹ -2 The areal capacitance at that time was 32.51 F cm⁻¹. -2 .

[0023] Example 4 Example 4 differs from Example 1 in that, in step (3), the reaction is carried out at 50°C for 0.5 h, while other preparation conditions and processes are the same as in Example 1, resulting in a nickel foam-supported NiCo-MOF electrode material. Figure 4 The curve shows that the electrode operates at 5 mA cm⁻¹ -2 The areal capacitance at that time was 22.53 F / cm². -2 .

[0024] Example 5 Example 5 differs from Example 1 in that, in step (3), the reaction is carried out at 50°C for 1.0 h, while other preparation conditions and processes are the same as in Example 1, resulting in a nickel foam-supported NiCo-MOF electrode material. Figure 4 The curve shows that the electrode operates at 5 mA cm⁻¹ -2 The area capacitance at that time was 35.34 F cm⁻¹. -2 .

[0025] Example 6 Example 6 differs from Example 1 in that, in step (3), the reaction is carried out at 50°C for 2.0 h, while other preparation conditions and processes are the same as in Example 1, resulting in a nickel foam-supported NiCo-MOF electrode material. Figure 4 The curve shows that the electrode operates at 5 mA cm⁻¹ -2 The area capacitance at that time was 29.76 F cm⁻¹. -2 .

[0026] Example 7 Example 7 differs from Example 1 in that, in step (3), the reaction is carried out at 50°C for 2.5 hours. Other preparation conditions and processes are the same as in Example 1, resulting in a nickel-foamed NiCo-MOF electrode material. Figure 4 The curve shows that the electrode operates at 5 mA cm⁻¹ -2 The area capacitance at that time was 25.66 F / cm². -2 .

[0027] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step (3), the reaction was carried out at room temperature for 0 hours, while other preparation conditions and processes were the same as in Example 1, resulting in nickel foam-supported NiCo-MOF electrode material. Figure 4 The curve shows that the electrode operates at 5 mA cm⁻¹ -2 The area capacitance at that time was 15.09 F cm⁻¹. -2 .

[0028] The nickel foam-supported micron-shaped NiCo-MOF electrode material prepared in Example 1 was tested at a current density of 5 mA cm⁻¹. -2The area capacitance is as high as 57.85 F / cm². -2 At a high current density of 50 mA cm -2 The capacitance retention rate is 75.13%, even at very high current densities of 150 mA / cm². -2 The areal capacitance is also as high as 27.07 F cm⁻¹. -2 The electrode materials prepared in Examples 2 to 7 were used at a current density of 5 mA cm⁻¹. -2 It also has a very high capacity (greater than 22.00 F / cm²). -2 And all of them are much higher than Comparative Example 1 (15.09F cm). -2 This indicates that soaking the nickel foam-supported micron-shaped NiCo-MOF electrode material at room temperature or 50°C before the solvothermal reaction can significantly improve the capacity and rate performance, while avoiding the use of binders. This allows it to be directly applied to next-generation high-performance supercapacitors and also shows promise in the fields of lithium-ion batteries and electrocatalysis.

[0029] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description and ideas. It is neither necessary nor possible to exhaustively describe all implementation methods here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A micron-sized flower-like NiCo-MOF electrode material, its preparation method, and its application, characterized in that, The preparation includes the following steps: (1) Dissolve Ni(NO3)2·6H2O, Co(NO3)2·6H2O and terephthalic acid powder reagents in N,N-dimethylformamide and deionized water, and stir with magnetic force and glass rod to obtain a uniform mixed solution. (2) The above mixed solution was transferred into the polytetrafluoroethylene liner of the reactor and acid-washed pretreated nickel foam was added. After the reactor was sealed, it was placed in a drying oven and soaked at a low temperature to obtain nascent nano-NiCo-MOF grown on the surface of the nickel foam. (3) The reaction vessel was heated to a high temperature in a forced-air drying oven to carry out a solvothermal reaction. After cooling to room temperature, the sample was taken out, washed with deionized water and anhydrous ethanol respectively, and then dried to obtain nickel foam supported nano-NiCo-MOF electrode material. In step (1), the molar ratio of Ni(NO3)2·6H2O, Co(NO3)2·6H2O and terephthalic acid in the mixed solution is 2:1:2; Further, in step (1), the concentrations of Ni(NO3)2·6H2O, Co(NO3)2·6H2O, and terephthalic acid in the mixed solution are 0.05, 0.025, and 0.05 mol / L, respectively. -1 ; In step (1), the mixed solution is obtained by adding a certain volume of N,N-dimethylformamide solution to the three powder reagents, stirring magnetically for 20 minutes until completely dissolved, then adding a certain volume of deionized water, stirring with a glass rod for 2 minutes, and finally obtaining a uniform mixed solution. In step (1), the volume ratio of N,N-dimethylformamide to deionized water in the mixed solution is 9:

1.

2. The preparation method according to claim 1, characterized in that, In step (2), the soaking reaction temperature is 10~60°C and the reaction time is 0.5~4h.

3. The preparation method according to claim 1, characterized in that, In step (3), the solvothermal reaction temperature is 150°C and the reaction time is 14h.

4. A micron-shaped NiCo-MOF electrode material synthesized by the preparation method according to any one of claims 1-3, characterized in that, The micron-flower-like NiCo-MOF electrode material has a unique three-dimensional layered structure, including a bottom layer of honeycomb nanosheet array and an outer layer of micron-flower array composed of a large number of nanosheets stacked together, which are grown in situ on a nickel foam substrate.

5. The application of the micron-shaped NiCo-MOF electrode material synthesized by the preparation method according to any one of claims 1-4 can be directly applied to the next generation of high-performance supercapacitors, and also has certain application prospects in the fields of lithium-ion batteries and electrocatalysis.